Preparation method of boron-nitrogen co-doped carbon material and application of boron-nitrogen co-doped carbon material in electrochemistry

By using cheap natural bio-based carbon sources and high-speed shear homogenization and spray drying processes, combined with high-temperature pyrolysis treatment, high-performance boron-nitrogen co-doped carbon materials were prepared, which solved the problems of poor doping uniformity and poor electrical performance, and achieved efficient and low-cost electrochemical performance improvement.

CN119898752APending Publication Date: 2025-04-29UNIV OF ELECTRONICS SCI & TECH OF CHINA +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510067078.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The doping uniformity of existing boron and nitrogen co-doped carbon materials is poor and the electrical performance is poor.

Method used

Inexpensive natural bio-based carbon sources, such as walnut shells, shrimp shell powder, etc., are used to prepare high-performance boron-nitrogen co-doped carbon materials through high-speed shear homogenization and spray drying processes, combined with high-temperature pyrolysis treatment.

Benefits of technology

Improves the doping uniformity and electrochemical properties of the material, enhances catalytic activity, and reduces production costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898752A_ABST
    Figure CN119898752A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a boron-nitrogen co-doped carbon material, which comprises the following steps: 1) dissolving a carbon source, a boron source and a nitrogen source in a mixed solvent, stirring and pre-dispersing, adding a dispersing agent, continuously stirring and dispersing uniformly, and dispersing by high-speed shearing to obtain a mixed solution; 2) carrying out spray drying on the mixed solution in the step 1), and screening to obtain precursor powder; and 3) carrying out high-temperature pyrolysis treatment on the product obtained in the step 2), and then cooling and grinding to obtain the boron-nitrogen co-doped carbon material. The invention also discloses an application of the boron-nitrogen co-doped carbon material in electrochemistry. The boron and nitrogen co-doped carbon material which is compact in structure and uniform in boron and nitrogen doping is prepared by adopting a natural bio-based carbon source and combining high-speed shearing dispersion, spray drying and high-temperature pyrolysis treatment, and the boron and nitrogen co-doped carbon material has relatively high specific capacitance and better and excellent rate capability and energy storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical energy storage materials, and specifically relates to a preparation method of a boron-nitrogen co-doped carbon material and its application in electrochemistry. Background Art

[0002] Boron and nitrogen co-doped carbon nanomaterials have shown broad application prospects in energy storage, catalysis, sensing and other fields due to their unique physical and chemical properties. This type of material can significantly improve the electrical conductivity, chemical stability and electrochemical activity of the material by introducing boron (B) and nitrogen (N) elements into the carbon nanostructure. The co-doping of boron and nitrogen can increase the defects and active sites of the material, thereby enhancing its performance in the electrochemical process, especially in the field of electrochemical energy storage and conversion such as supercapacitors and batteries.

[0003] In the prior art, the preparation of boron and nitrogen co-doped carbon usually adopts the following methods: high temperature pyrolysis, chemical vapor deposition, solvent thermal, hydrothermal and template method.

[0004] Among them, (1) high-temperature pyrolysis method: After mixing the boron and nitrogen-containing precursor with a carbon source, pyrolysis is carried out at high temperature in an inert atmosphere to generate a doped material. This method takes a long time to react, usually requiring several hours to dozens of hours of high-temperature treatment, and has low preparation efficiency; boron and nitrogen are easy to volatilize or migrate at high temperatures, resulting in unstable doping levels; the high-temperature environment needs to be maintained for a long time, increasing costs and energy consumption; the precursor may decompose at high temperatures to generate impurities, affecting the purity and performance of the material.

[0005] (2) Chemical vapor deposition (CVD): Under high temperature conditions, a gas precursor containing boron and nitrogen (such as triethylborane, ammonia, etc.) and a carbon gas source are co-deposited on the surface of the substrate to form a boron-nitrogen co-doped carbon material. This method requires expensive high-temperature reactors and precision control systems, making it difficult to achieve low-cost large-scale production; the reaction is usually slow, and the preparation yield is much lower than other methods; although the CVD method can fine-tune the material morphology, the uniformity of doping and the repeatability of the structure are difficult to achieve; the reaction requires precise control of temperature and atmosphere, and the process requirements are strict.

[0006] (3) Solvothermal / hydrothermal method: Boron and nitrogen compounds are mixed with carbon sources in a solution, a precursor is generated through chemical reaction, and then carbonization is performed to form a co-doped material. In the solution method, the doping elements are easily lost or unevenly dispersed, resulting in low or uneven concentrations of boron and nitrogen; the controllability of the solution reaction is poor, and it is difficult to form a specific nanostructure; it is difficult to scale up production due to the limitation of reactor volume and post-processing steps; it usually requires multiple steps (such as solution reaction, hydrothermal, drying, carbonization), and it takes a long time.

[0007] (4) Template method: The morphology of the carbon material is guided by a hard template (such as silica, alumina) or a soft template (such as a surfactant), and then doping is achieved through a precursor containing boron and nitrogen, and finally the template is removed to obtain the material. This method requires acid washing or high-temperature calcination to remove the template, which may introduce impurities or destroy the structure. The preparation and post-processing steps of the template are complicated and the overall cost is high. A large amount of waste liquid or waste gas may be generated during the template removal process, which is not environmentally friendly. The template method often requires multi-step processing and a long preparation cycle. Summary of the invention

[0008] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a method for preparing a boron-nitrogen co-doped carbon material, which aims to solve the problems of poor doping uniformity and poor electrical performance of the existing boron-nitrogen co-doped carbon material.

[0009] The main purpose of the present invention is to provide the application of the boron-nitrogen co-doped carbon material in electrochemistry.

[0010] The objective of the present invention is achieved through the following technical solutions:

[0011] A method for preparing a boron-nitrogen co-doped carbon material comprises the following steps:

[0012] 1) dissolving a carbon source, a boron source and a nitrogen source in a mixed solvent, stirring and pre-dispersing them, adding a dispersant, continuing to stir and disperse them uniformly, and then dispersing them by high-speed shearing to obtain a mixed solution;

[0013] 2) spray drying the mixed solution in step 1) and sieving to obtain a precursor powder;

[0014] 3) The material in step 2) is subjected to high temperature pyrolysis treatment, followed by cooling and grinding to obtain a boron-nitrogen co-doped carbon material.

[0015] In some specific embodiments, the carbon source is one or more of walnut shells, shrimp shell powder, coffee grounds or cellulose.

[0016] In some specific embodiments, the boron source is one or more of boron powder, boric acid, borate or organic boron compound.

[0017] Furthermore, the borate is borax, and the organic boron compound is triethylborane.

[0018] In some embodiments, the nitrogen source is one or more of urea, melamine or polyacrylonitrile.

[0019] In some specific embodiments, the mass ratio of the carbon source, the boron source and the nitrogen source is (5-15):(0.5-1.5):(1.5-3).

[0020] In some specific embodiments, the high-speed shear dispersion in step 1) is specifically: using a high shear homogenizer, setting the processing time to 5-8 minutes, the rotation speed to 20000-30000rpm, the number of cycles to 1-3 times, the time interval between each processing to 2 minutes, and the temperature to 30-40°C.

[0021] In some specific embodiments, the mixed solvent is a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:(1-3), and the dispersant is one or more of polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA) and sodium citrate.

[0022] In certain specific embodiments, the spray drying conditions in step 2) are: inlet air temperature is 120-180°C, outlet air temperature is 60-100°C, spray pressure is 0.6-1.0 MPa, and spray flow rate is controlled at 0.8-1.2 L / h.

[0023] In some specific embodiments, the high temperature pyrolysis treatment in step 3) is specifically: under an inert atmosphere, at a heating rate of 50-100°C / s, the temperature in the furnace is controlled to rise rapidly from room temperature to 1500-1800°C within 10-20s, and then maintained at 1500-1800°C for 30-60s.

[0024] An application of the boron-nitrogen co-doped carbon material prepared by the above-mentioned preparation method in electrochemistry.

[0025] Compared with the prior art, the present invention has at least the following advantages:

[0026] 1) The present invention uses cheap and common natural bio-based carbon sources (walnut shells, shrimp shell powder, coffee grounds and cellulose) as biomass carbon sources, which belongs to the recycling of biomass waste. The natural bio-based carbon source has a relatively complex structure, including a large number of micropores and mesopores; during the high-temperature thermal shock process, the pore structure will be retained and further optimized; at the same time, the pore structure can not only increase the specific surface area of ​​the material, but also provide more surface active sites, which is conducive to the embedding and uniform distribution of boron and nitrogen elements; high porosity can also improve the electrochemical performance and catalytic activity of the material, because more reaction sites can increase the contact area of ​​the catalytic reaction; at the same time, the surface of the natural bio-based carbon source contains abundant oxidized groups (such as hydroxyl, carboxyl, aldehyde, etc.); these functional groups can not only form chemical bonds with boron and nitrogen sources, but also enhance the fixation and stability of the elements through interaction with doping elements. For example, carboxyl and hydroxyl groups may react chemically with nitrogen sources (such as urea) and boron sources (such as boric acid), promote the embedding of boron and nitrogen elements in the carbon structure, and improve the stability of the material.

[0027] 2) High-speed shear dispersion is adopted in the present invention. The high shear force generated by the high shear homogenizer can effectively break the aggregation between molecules, promote the uniform distribution of boron source and nitrogen source on the surface of carbon source, effectively improve the reactivity of raw materials, and provide more surface contact points for the dispersion and reaction of doping elements. In addition, high shear homogenizers usually do not involve high temperature, and the temperature can be controlled at 30-40°C to avoid overheating in the solution; therefore, the surface activity of the precursor can be improved while maintaining the original characteristics of the raw materials, thereby improving the stability of the precursor and the doping efficiency in the subsequent pyrolysis process. In addition, the spray drying method is adopted in the drying process of the present invention, which can significantly increase the drying speed, and while maintaining the uniformity and dispersibility of the particles, it reduces the agglomeration phenomenon and prevents the agglomeration between particles; because the temperature and humidity in the spray drying process can be precisely controlled, it can effectively avoid thermal degradation or decomposition of certain temperature-sensitive components during the drying process; in addition, the spray dryer can also adapt to large-scale production, has certain industrialization potential, and is particularly suitable for high-yield production. The present invention provides a stable precursor for preparing high-performance boron-nitrogen co-doped carbon materials through the combination of high-shear homogenization and spray drying, thereby ensuring the uniformity and stability of the precursor powder.

[0028] 3) The high-temperature pyrolysis treatment of the present invention adopts a high-temperature thermal shock process. First, it can quickly increase the temperature to the required reaction temperature in a very short time and complete the reaction in a short time, greatly improving the reaction rate; in addition, the high-temperature thermal shock can promote the rapid reaction of the carbon source, boron source and nitrogen source, and cause a local thermal gradient effect through rapid temperature changes; this temperature gradient effect causes the reactants to experience different local temperature environments at different reaction stages, thereby guiding the selection of different reaction paths (for example, the introduction of nitrogen and boron may form a more stable chemical bonding mode through rapid changes in thermal shock, such as nitrogen doping can form a more stable NC bond with carbon, and boron can stably exist in the carbon-based structure, avoiding excessive reaction or secondary reaction that may be caused by long-term heating). Furthermore, the short time and high temperature change characteristics of the high-temperature thermal shock process significantly improve the diffusion rate of substances, especially in the interaction between carbon sources, boron sources and nitrogen sources, which can reduce the diffusion time between reactants, thereby accelerating the reaction, so that boron and nitrogen sources can be uniformly doped into carbon-based materials in a shorter time, overcoming the problems of uneven doping and instability of reaction intermediates caused by long-term reaction in conventional high-temperature treatment processes; finally, through high-temperature thermal shock, the reaction can be completed in a short time, the doping state of boron and nitrogen can be quickly fixed, the occurrence of side reactions can be avoided, and the adverse interactions between reactants can be effectively reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.

[0030] Figure 1 This is a SEM image of the boron-nitrogen co-doped carbon material prepared in Example 1 and Example of the present invention;

[0031] Figure 2 CV curves of the boron-nitrogen co-doped carbon materials prepared in Example 1 and Example of the present invention;

[0032] Figure 3 This is a GCD curve diagram of the boron-nitrogen co-doped carbon material prepared in Example 1 and Example of the present invention. DETAILED DESCRIPTION

[0033] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0034] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values ​​with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values ​​listed herein include the endpoints of the range, and all integers and fractions within the range.

[0035] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.

[0036] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.

[0037] In the present application, the carbon source is one or more of walnut shells, shrimp shell powder, coffee grounds and cellulose, and its main function is to provide a carbon skeleton for subsequent high-temperature pyrolysis treatment (carbonization);

[0038] For example, walnut shells, as natural organic matter, have a relatively complex structure, including a large number of micropores and mesopores. During the high-temperature thermal shock process, the pore structure will be retained and further optimized. At the same time, the pore structure can not only increase the specific surface area of ​​the material, but also provide more surface active sites, which are conducive to the embedding and uniform distribution of boron and nitrogen elements. High porosity can also improve the electrochemical performance and catalytic activity of the material, because more reaction sites can increase the contact area of ​​the catalytic reaction. At the same time, the surface of walnut shells contains abundant oxidized groups (such as hydroxyl, carboxyl, aldehyde, etc.). These functional groups can not only form chemical bonds with boron and nitrogen sources, but also enhance the fixation and stability of the elements through interaction with doping elements. For example, carboxyl and hydroxyl groups may react chemically with nitrogen sources (such as urea) and boron sources (such as boric acid), promote the embedding of boron and nitrogen elements in the carbon structure, and improve the stability of the material.

[0039] The boron source is one or more of boron powder, boric acid, borate or organic boron compound, and the boron source mainly provides boron element to ensure the stable supply of boron element;

[0040] The nitrogen source is one or more of urea, melamine or polyacrylonitrile, which functions to provide nitrogen-rich organic structures;

[0041] The mixed solvent is a mixture of anhydrous ethanol and deionized water, and the main function of the mixed solvent is to be used for dispersion and mixing.

[0042] The present invention also provides a method for preparing the boron-nitrogen co-doped carbon material, comprising the following steps:

[0043] 1) dissolving a carbon source, a boron source and a nitrogen source in a mixed solvent, stirring and pre-dispersing them, adding a dispersant, continuing to stir and disperse them uniformly, and then dispersing them by high-speed shearing to obtain a mixed solution;

[0044] 2) spray drying the mixed solution in step 1) and sieving to obtain a precursor powder;

[0045] 3) The material in step 2) is subjected to high temperature pyrolysis treatment, followed by cooling and grinding to obtain a boron-nitrogen co-doped carbon material.

[0046] When the high shear homogenizer is working, its rotor rotates at high speed to generate strong shear force, centrifugal force and high-frequency mechanical vibration; these forces are applied to the mixed system containing boron, nitrogen source and carbon source, which can forcibly break up the agglomerated material particles, so that the precursor compounds of boron and nitrogen elements and the carbon source can be fully contacted and mixed. For example, for some boron source powders with large initial agglomeration particle size, under the action of high shear force, the agglomerate structure is destroyed, and single particles or smaller agglomerates are evenly dispersed in the carbon source solution or suspension, which ensures the initial uniformity of element distribution from the source. The high shear process is not only a simple physical mixing, but also affects the structure at the molecular level. Due to the continuous action of shear force, some carbon chain structures will be broken and reorganized to form active sites that are more conducive to boron and nitrogen doping. Boron and nitrogen precursor compounds are more efficiently adsorbed and reacted around these active sites, which in turn promotes the generated doping precursor to be more regular and uniform in microstructure. Under the action of high shear, the chemical bonds on the surface of the carbon source are activated, and the boron and nitrogen precursors are chemically bonded to it, avoiding local over-doping or under-doping, so that the overall microstructure of the precursor tends to be consistent. At the same time, the mixed liquid after high shear homogenization is atomized into tiny droplets through the nozzle, and these droplets enter the hot air flow to quickly evaporate water. Due to the extremely small droplet size and uniform initial composition (thanks to high shear homogenization), during the drying process, the precursor of the boron and nitrogen co-doped carbon material nucleates and grows at a nearly synchronous rate. Each tiny droplet is like an independent "microreactor", and the precursor particles formed inside are highly consistent in the initial nucleation conditions, avoiding uneven composition due to local environmental differences. For example, when the solvent in the droplets begins to evaporate, boron, nitrogen, and carbon elements precipitate to form precursors according to the established chemical equilibrium relationship, and there will be no uneven phenomenon caused by the preferential precipitation of boron in a certain area; during the spray drying process, the hot air flow not only takes away the moisture, but also plays a "setting" role on the formed precursor particles; and then the surface of the particles is quickly solidified through rapid drying, preventing further agglomeration between particles and disordered diffusion of the internal structure. Compared with traditional drying methods, traditional methods have slow drying speeds, and the particles are in a semi-wet state for a long time, which makes it easy for them to adhere to each other and deform under the action of gravity, surface tension, etc., resulting in different sizes of precursor powder particles and unstable structures. However, due to its rapidity, spray drying ensures that the precursor particles maintain a relatively stable spherical or quasi-spherical shape once formed, and the internal structure of the particles is dense and stable, which ensures the stability of the precursor from both morphological and structural aspects.

[0047] Compared with traditional mechanical stirring, it is a more common mixing method. In this method, the shear force of the stirring paddle is relatively weak. For some raw materials with strong agglomeration, such as the mixing of boron source and carbon source, it is difficult to fully break up the agglomerates. Although ultrasonic dispersion can improve the mixing effect to a certain extent, it mainly disperses the particles through cavitation. However, the scope and intensity of this effect are limited. For complex multiphase systems, especially when there is interaction between boron, nitrogen source and carbon source leading to agglomeration, ultrasonic dispersion may not ensure uniform mixing of all raw materials at the microscopic scale; and ultrasonic dispersion may introduce problems such as local overheating, affecting the stability of the material. High shear homogenization can comprehensively mix the raw materials at the macroscopic and microscopic scales without causing local overheating problems, which is conducive to the formation of uniform and stable precursors. For the drying process, traditional oven drying is to place the mixed solution in an oven to slowly evaporate the solvent. In this process, the solution forms a thick liquid layer at the bottom of the container, and the solvent evaporation starts from the surface, which causes the solute (i.e., the precursor component) to migrate during the drying process. For example, compounds of boron and nitrogen may gather to the edge or surface as the solvent evaporates, thereby causing an uneven distribution of precursor components. Moreover, the long slow drying process allows the precursor particles to have enough time to contact and agglomerate with each other, changing the morphology and size distribution of the particles and reducing the stability of the precursor. In contrast, the spray drying in the present application is to atomize the solution into tiny droplets, each droplet is dried independently, avoiding the problems of solute migration and excessive agglomeration of particles, and better maintaining the stability of the precursor; although vacuum drying can speed up the drying speed, for some viscous precursor solutions, under a vacuum environment, the escape of bubbles inside the solution may cause the solution to turn over and the uneven distribution of components. In addition, after the precursor powder after vacuum drying is taken out from the vacuum environment, due to the change of environmental pressure, the powder structure may be affected, such as the collapse of the pore structure, which affects the stability of the precursor. The precursor particle structure after spray drying has been stably formed during the drying process, and will not be disturbed by factors such as subsequent environmental pressure changes, which is more conducive to maintaining a uniform and stable state.

[0048] In some specific embodiments, the high-speed shear dispersion in step 1) is specifically: using a high shear homogenizer, setting the processing time to 5-8 minutes, the rotation speed to 20000-30000rpm, the number of cycles to 1-3 times, the time interval between each processing to 2 minutes, and the temperature to 30-40°C.

[0049] In certain specific embodiments, the spray drying conditions in step 2) are: inlet air temperature is 120-180°C, outlet air temperature is 60-100°C, spray pressure is 0.6-1.0 MPa, and spray flow rate is controlled at 0.8-1.2 L / h.

[0050] In some specific embodiments, the high temperature pyrolysis treatment in step 3) is specifically: under an inert atmosphere, at a heating rate of 50-100°C / s, the temperature in the furnace is controlled to rise rapidly from room temperature to 1500-1800°C within 10-20s, and then maintained at 1500-1800°C for 30-60s.

[0051] Inert atmosphere can prevent the precursor powder from oxidizing at high temperature, ensuring the purity and structural stability of the boron-nitrogen co-doped carbon material. Start the equipment, and the precursor powder soars from room temperature to the set high temperature in a very short time (about 10-20 seconds). It is subjected to severe thermal shock, causing the internal chemical bonds to break and reorganize quickly, completing the carbonization of the carbon material and the deep doping process of boron and nitrogen elements. After reaching the target temperature, maintain this high temperature state for 30-60 seconds for insulation to ensure sufficient reaction and uniform and stable material structure, so that boron and nitrogen atoms have enough time to accurately embed into the carbon lattice to form a stable doping structure. After the insulation is completed, cut off the heating power supply, keep the argon gas flowing continuously, and use the natural heat dissipation of the furnace to quickly cool the product to room temperature in an inert atmosphere. This process can effectively avoid the high-temperature product from contacting with the air for oxidation and structural defects caused by sudden cooling.

[0052] It should also be noted that the technical solution of the present invention greatly shortens the preparation cycle by achieving high-temperature thermal shock through the use of an ultra-high heating rate. The traditional pyrolysis method often requires several hours of slow heating and constant temperature reaction, while the total time of this preparation method can be controlled within a few minutes, which significantly improves production efficiency and meets the needs of large-scale industrial rapid preparation. The rapid thermal shock prompts boron and nitrogen atoms to be efficiently and evenly embedded in the carbon skeleton under thermal drive, avoiding the problem of uneven doping caused by differences in element diffusion rates during conventional slow pyrolysis, improving the overall conductivity and chemical stability of the material, and optimizing its working performance in application scenarios such as electronic devices and battery electrodes.

[0053] Example 1

[0054] This embodiment provides a method for preparing a boron-nitrogen co-doped carbon material, which comprises the following steps:

[0055] 1) Preparation of precursor

[0056] 11) 20 g of walnut shell powder (after washing and drying the discarded walnut shells, use a grinder to crush them into 200 mesh powder to obtain walnut shell powder for later use), 2 g of boron powder (analytical grade, purity ≥99.5%), and 4 g of urea (industrial grade, purity ≥99%) are placed together in 150 mL of a mixed solvent of deionized water and ethanol (the solvent ratio is water: ethanol = 1.5:1), and stirred and pre-dispersed on a magnetic stirrer to obtain a uniform precursor solution;

[0057] 12) Add 1 g of dispersant PVP (polyvinyl pyrrolidone) to the precursor solution, continue stirring and dispersing until uniform, to obtain a mixed solution A;

[0058] 13) transferring the mixed solution A to a high shear homogenizer, setting the operating parameters to a rotation speed of 20,000 rpm, a treatment time of 5 minutes, standing for 30 seconds after each treatment and repeating 3 times to ensure that the boron source, nitrogen source and carbon source are fully dispersed, and obtaining a homogenized mixed solution B;

[0059] 14) The homogenized mixed solution B is then transferred into a spray dryer, the inlet air temperature is set to 160° C., the outlet air temperature is set to 80° C., the spray pressure is set to 0.8 MPa, the spray flow rate is controlled at 1.0 L / h, and spray drying is started to obtain a pre-precursor powder;

[0060] 15) The pre-precursor powder after spray drying is collected by a separator, and the collected pre-precursor powder is sieved to obtain a precursor powder with a particle size of 10-100 μm.

[0061] 2) Synthesis of boron and nitrogen co-doped carbon materials

[0062] 21) Take 10 g of the precursor powder prepared in step 1) and carefully fill it into a high-purity graphite crucible (inner diameter 4 cm, depth 3 cm). The filling height is about 2 / 3 of the crucible depth. Gently shake the crucible to make the precursor powder flat and compact.

[0063] 22) Place the graphite crucible in a high-temperature furnace, seal the furnace cavity, introduce argon (purity ≥ 99.99%), adjust the flow rate to 120 mL / min, exhaust the air in the furnace, and create an oxygen-free environment;

[0064] 23) Turn on the equipment and set the heating program. At a heating rate of 80°C / s, the temperature in the furnace is rapidly raised from room temperature to 1600°C within 15 seconds. After reaching the pyrolysis temperature of 1600°C, keep it warm for 45 seconds to allow the boron and nitrogen atoms to be fully embedded in the carbon skeleton under strong thermal drive to complete the carbonization and doping process. After cooling, break and grind the black block material in the crucible to collect the boron-nitrogen co-doped carbon material.

[0065] Example 2

[0066] This embodiment provides a method for preparing a boron-nitrogen co-doped carbon material, which is basically the same as that of Embodiment 1, except that different carbon sources, nitrogen sources and boron sources are used, specifically:

[0067] 11) 20 g of coffee grounds powder (the coffee grounds were first dried at 80° C. for 4 hours and then crushed into 200 mesh powder to obtain coffee grounds powder for later use), 2 g of boric acid (analytical grade, purity ≥ 99%), and 4 g of melamine (analytical grade, purity ≥ 99%) were placed together in 150 mL of a mixed solvent of deionized water and ethanol (the solvent ratio was water: ethanol = 1.5:1), and stirred and pre-dispersed on a magnetic stirrer to obtain a uniform precursor solution;

[0068] The remaining steps 12), 13), 14), 15) in step 1) and step 2) are consistent with those in Example 1.

[0069] Example 3

[0070] This embodiment provides a method for preparing a boron-nitrogen co-doped carbon material, which is basically the same as that of Embodiment 1, except that different carbon sources, nitrogen sources and boron sources are used, specifically:

[0071] 11) 20 g of shrimp shell powder (abandoned shrimp shell powder is selected as the carbon source, washed, dried at 100° C. to constant weight, and then crushed into 200 mesh powder to obtain shrimp shell powder for standby use), 2 g of triethylborane (analytical grade, purity ≥99%), and 4 g of hexamethylenetetramine (industrial grade, purity ≥99%) are placed together in 150 mL of a mixed solvent of deionized water and ethanol (the solvent ratio is water: ethanol = 1.5:1), and stirred and pre-dispersed on a magnetic stirrer to obtain a uniform precursor solution;

[0072] The remaining steps 12), 13), 14), 15) in step 1) and step 2) are consistent with those in Example 1.

[0073] Example 4

[0074] This embodiment provides a method for preparing a boron-nitrogen co-doped carbon material, which is basically the same as that of Embodiment 1, except that the heating rate in step 2) is different, specifically:

[0075] 23) Turn on the equipment and set the heating program. At a heating rate of 100°C / s, the temperature in the furnace is rapidly raised from room temperature to 1600°C within 10 seconds. After reaching the pyrolysis temperature of 1600°C, keep it warm for 55 seconds to allow the boron and nitrogen atoms to be fully embedded in the carbon skeleton under strong thermal drive to complete the carbonization and doping process. After cooling, break and grind the black block material in the crucible to collect the boron-nitrogen co-doped carbon material.

[0076] The rest of 1) and 21) and 22) in step 2) are consistent with those in Example 1.

[0077] Example 5

[0078] This embodiment provides a method for preparing a boron-nitrogen co-doped carbon material, which is basically the same as that of Embodiment 1, except that the heating rate in step 2) is different, specifically:

[0079] 23) Turn on the equipment and set the heating program. At a heating rate of 60°C / s, the temperature in the furnace is rapidly raised from room temperature to 1600°C within 25 seconds. After reaching the pyrolysis temperature of 1600°C, keep warm for 40 seconds to allow the boron and nitrogen atoms to be fully embedded in the carbon skeleton under strong thermal drive to complete the carbonization and doping process. After cooling, break and grind the black block material in the crucible to collect the boron and nitrogen co-doped carbon material.

[0080] The rest of 1) and 21) and 22) in step 2) are consistent with those in Example 1.

[0081] Comparative Example 1

[0082] This comparative example provides a method for preparing a boron-nitrogen co-doped carbon material, which is basically the same as Example 2, except that: the heating rate and / or holding time are changed, and it is found that when the heating rate is too slow (such as less than 30°C / s), the diffusion rate of boron and nitrogen elements will be delayed, resulting in uneven doping and affecting the electrochemical properties of the material; at high temperatures, the reaction and embedding process between boron, nitrogen elements and the carbon source requires a certain amount of time; if the holding time is insufficient (20s), the doping elements will not have sufficient time to combine with the carbon source, resulting in poor doping effect and poor stability of the material; on the contrary, too long a holding time (such as 75s) will lead to excessive heat transfer, affecting the microstructure of the material, and may even cause excessive carbonization.

[0083] Performance test example:

[0084] 1) Appearance

[0085] The present application conducted microscopic morphology testing on the boron-nitrogen co-doped carbon materials prepared in Example 1 and Example 2, and the SEM images thereof are as follows: Figure 1 As shown in the figure, it can be seen that the microscopic morphology of the boron-nitrogen co-doped carbon material prepared by the preparation method of the present application is composed of a large number of irregular nanoparticles, the particles are tightly stacked with almost no obvious gaps, forming a relatively dense structure.

[0086] 2) Rate performance test

[0087] The electrical properties of the boron-nitrogen co-doped carbon materials prepared in Example 1 and Example 2 were tested in this application, wherein the rate test method was:

[0088] The prepared boron-nitrogen co-doped carbon material and conductive carbon black were weighed in a mass ratio of 9:1 and placed in a centrifuge tube. A solution of water and ethanol in a volume ratio of 1:1 was measured as a solvent. 5% of the solvent volume of 5wt% Nafion was added as a binder. The centrifuge tube was placed in a cell crusher for 30 seconds per cycle, for a total of 5 cycles, with a 10-second interval between each cycle to process the material to form a uniform dispersion. The above dispersion was sprayed on a 1×1 cm 2 The prepared working electrode was dried in an oven at 40°C as a working electrode; the prepared working electrode, a platinum counter electrode and a mercury / mercury oxide reference electrode were used to form a three-electrode system for relevant electrochemical performance tests in 6M KOH; first, cyclic voltammetry (CV) tests were performed on Examples 1 and 2, with a test voltage range of -1 to 0 V and a scan rate range of 5 to 200 mA / cm relative to the mercury / mercury oxide electrode. 2 ; Then, constant current charge-discharge (GCD) test was performed on Examples 1 and 2.

[0089] Results and Discussion:

[0090] Test data such as Figure 2 As shown, Figure 2 The CV curves of Examples 1 and 2 are shown below. The left side shows Example 1, and the right side shows Example 2. The CV curves of Examples 1 and 2 have obvious redox peaks, indicating that when boron and nitrogen are co-doped, a Faraday reaction occurs in the electrode, that is, pseudocapacitance behavior exists. Pseudocapacitance is based on a rapid redox reaction on the electrode surface, involving electron transfer. This redox reaction can store and release more charge, thereby improving capacitance performance. The integral area of ​​the CV curve of Example 1 is greater than that of Example 2, indicating that at the same scanning speed, the example can store and release more charge in one potential scanning cycle, which means a higher specific capacitance. Example 1 and Example 2 at 1Ag -1 At a current density of , the specific capacitance of the electrodes is 365.1F / g and 306.3F / g respectively. Figure 3 ); and this performance is achieved at different scanning speeds, which also shows that the capacitance performance of Example 1 is more advantageous than that of Example 2 under different scanning conditions, and its charge storage and release capabilities may be relatively less affected by changes in scanning speed, that is, Example 1 may have better rate performance.

[0091] 3) Energy storage test

[0092] Test method: see magnification test

[0093] Results and Discussion

[0094] Test data such as Figure 3 As shown, Figure 3The GCD curves of Examples 1 and 2 are shown in Figure 1. The left side is Example 1, and the right side is Example 2. In Examples 1 and 2, the GCD curves at different current densities are similar in shape; all curves show asymmetric shapes, which further indicates that Examples 1 and 2 have pseudocapacitive behavior during the charge and discharge process. As the current density increases (from -1A g -1 Up to 20A g -1 ), the charge and discharge time is significantly shortened. This is because at a higher current density, the reaction rate on the electrode surface is accelerated, and the charge is quickly stored and released on the electrode surface, but it also leads to an increase in electrode polarization, which shortens the charge and discharge time; comparing the charge and discharge time of Examples 1 and 2 at the same current density, this means that Example 1 has a better charge storage capacity at a lower current density.

[0095] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A method for preparing a boron-nitrogen co-doped carbon material, characterized in that: The steps include: 1) dissolving a carbon source, a boron source and a nitrogen source in a mixed solvent, stirring and pre-dispersing them, adding a dispersant, continuing to stir and disperse them uniformly, and then dispersing them by high-speed shearing to obtain a mixed solution; 2) spray drying the mixed solution in step 1) and sieving to obtain a precursor powder; 3) The material in step 2) is subjected to high temperature pyrolysis treatment, followed by cooling and grinding to obtain a boron-nitrogen co-doped carbon material.

2. The method for preparing a boron-nitrogen co-doped carbon material according to claim 1, characterized in that: The carbon source is one or more of walnut shells, shrimp shell powder, coffee grounds or cellulose.

3. The method for preparing the boron-nitrogen co-doped carbon material according to claim 1, characterized in that: The boron source is one or more of boron powder, boric acid, borate or organic boron compound.

4. The method for preparing a boron-nitrogen co-doped carbon material according to claim 1, characterized in that: The nitrogen source is one or more of urea, melamine or polyacrylonitrile.

5. The method for preparing a boron-nitrogen co-doped carbon material according to claim 4, characterized in that: The mass ratio of the carbon source, the boron source and the nitrogen source is (5-15):(0.5-1.5):(1.5-3).

6. The method for preparing a boron-nitrogen co-doped carbon material according to claim 1, characterized in that: The mixed solvent is a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:(1-3), and the dispersant is one or more of polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA) and sodium citrate.

7. The method for preparing a boron-nitrogen co-doped carbon material according to claim 4, characterized in that: The spray drying conditions in step 2) are: inlet air temperature is 120-180°C, outlet air temperature is 60-100°C, spray pressure is 0.6-1.0 MPa, and spray flow rate is controlled at 0.8-1.2 L / h.

8. The method for preparing a boron-nitrogen co-doped carbon material according to claim 1, characterized in that: The high temperature pyrolysis treatment in step 3) is specifically as follows: in an inert atmosphere, at a heating rate of 50-100°C / s, the temperature in the furnace is controlled to rise rapidly from room temperature to 1500-1800°C within 10-20s, and then maintained at 1500-1800°C for 30-60s.

9. Use of the boron-nitrogen co-doped carbon material prepared by the preparation method according to any one of claims 1 to 8 in electrochemistry.